Preparation of colloidal metals of iron group with uncapped surface in polar aprotic medium - Kolesnichenko, V.L.; Vu, V.; Goloverda, G. (Украинский химический журнал, 2005)
A novel method of preparation of the nanoscale Fe, Co and Ni metals in colloidal form and as nanopovvders is based on reduction of metal halides with sodium naphthalide in solutions of N-methyl pyrrolidone (NMPO). Room temperature reactions followed by solution annealing at 170—200 °C result in formation of uncapped nanoparticles of iron and cobalt metals and nickel carbide Ni3C. Colloidal metallic nickel was obtained in reaction of colloidal iron with NiCl2 in NMPO solutions. The surface of the obtained metallic nanoparticles is capable of chemical derivatization; their post-synthesis reaction with oleic acid resulted in hydrocarbon-soluble products.